Recapturing the meaning of Akhlāq Islamiyah: an analysis of the article “akhlak” in the Encyclopedia of Islam - Awang Abd. Rahman @ Jusoh, Amilah (IIUM Press, International Islamic University Malaysia, 2018)
This paper will analytically study the Islamic meaning of akhlaq as portrayed by two Western writers in the article entitled “Akhlak” published in the Encyclopedia of Islam. The author highlights the contribution of Western scholars especially Walzer and Gibb to the understanding of history of the development of Islamic thought and disciplines. By employing the qualitative methodology, the author uses textual analysis and comparative method on the writings of both thinkers and others. Findings indicate that there are several weaknesses in the writing that include limiting the scope of akhlaq to practical ethics of selected virtues, the lacking of clear detachment between akhlaq and ethical thought, and others.